It's Not Only Rents: Explaining the Persistence and Change of Neopatrimonialism in Indonesia - Nina Korte (German Institute of Global and Area Studies (GIGA), 2011)
Indonesia has long been associated with neopatrimonialism, corruption, collusion, and nepotism as the main modi operandi of politics, economics and public administration. Despite various measures and initiatives to fight these practises, little evidence for a significant decline can be found over the years. Rather, longitudinal analysis points to changes in the character of neopatrimonialism. Based on more than 60 in-depth interviews, focus-group discussions, and the analysis of both primary and secondary data, the aim of this article is, first, to describe the changes that have taken place, and, second, to investigate what accounts for these changes. Political economy concepts posit the amount and development of economic rents as the explanatory factor for the persistence and change of neopatrimonialism. This study's findings, however, indicate that rents alone cannot explain what has taken place in Indonesia. Democratisation and decentralisation exert a stronger impact.
Keywords: 300; Economic Rents; Neopatrimonialism; Democratisation; Decentralisation; Indonesia